(untitled) (GEON Journal (Management, Organizations and Business), 2021)
Troublesome: Mexico has an unmatched cultural wealth that includes beliefs, traditions and values. One of its main attractaions are its towns, within which the Secretary of Tourism has recognized since 2001, the most representative with a distinctive called: Magital towns. Objetive: this research study assesses the impact of the aforementioned program in the municipality of Valladolid, Yucatán, México and discusses its effects on the local economy. Materials and methods: the study contemplad the realization of survey by personal interview to autorities of the current administration of H. City Council of Valladolid and of the previous administration, businessmen, citizens and national and foreign tourists. Results and discussion: einding that a large part of the economic benefits generated by tourism is taken advantage of by tourism chains, which sell armed packages, affecting local companies. Conclusions: the challenge for the autorities, businessmen and citizens of the municipality today is to promete the distinctive by making synergy, that is, integrating its resources for the same purpose, promoting the recognition of the municipality as a magical town to the tourist markets of the country and the foreigner, which is expected to translate into an improvement of the local economy, which includes enterpreneurs and citizen, reinforcing one of the original purposes of the program, which is to raise the quality of life of citizens by obtaining better incomes from of tourism.